Effectiveness of the Innovative Matrix Strategy in the Achievement of Students in the Department of Artistic Education in the Subject of Arabic Calligraphy - Multaqa Nassir Jabbar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The aim of the current study was to examine the effectiveness of the Innovative Matrix Strategy in improving the academic achievement of students in the Department of Artistic Education in the subject of Arabic Calligraphy. The researcher formulated the null hypothesis that there is no statistically significant difference at the (0.05) significance level between the mean scores of the experimental group, who were taught using the Innovative Matrix Strategy, and the mean scores of the control group, who were taught using the traditional method, in the post-test achievement test. She used the experimental method and the partial control experimental design, which included two groups. They are namely experimental and control groups with a post-test to assess achievement. The study community consisted of third-year students in the Departments of Artistic Education in the Colleges of Basic Education across all Iraqi universities for the academic year (2024 – 2025), with a total of two departments (Al-Mustansiriya University and University of Misan,). The sample of this study consisted of (61) students, including (30) in the experimental group and (31) in the control group. The researcher ensured equivalence between the two groups in terms of chronological age (calculated in months) and intellectual ability (IQ test). She also developed an achievement test consisting of (45) items distributed across the curriculum topics. After verifying its validity and reliability, the test was applied to the sample of this study. After conducting the statistical analysis, She concluded that the students in the experimental group, who were taught using the Innovative Matrix Strategy, performed better in material of the Arabic Calligraphy than the students in the control group who were taught using the traditional method. This provides clear evidence of the effectiveness of this strategy in improving the academic achievement of the study sample students